Penerapan Metode Rank Order Centroid dan SMART Dalam Sistem Pendukung Keputusan Pemilihan Waitress Terbaik - Puspa Citra; Muhammad Najib Dwi Satria (PT. Tech Cart Press, 2024)
The main duties of a waitress include welcoming and directing customers to tables, taking food and beverage orders, serving dishes, and ensuring customer satisfaction during their visit. One of the main problems in determining the best waitress is finding a balance between technical skills, such as the ability to take orders quickly. The main problem in determining the best waitress is finding a balance between technical skills, such as the ability to take orders quickly or manage tables efficiently, and interpersonal skills, such as good communication skills and the ability to maintain positive relationships with customers. In addition, attention also needs to be paid to the ability to work in demanding situations, maintain cleanliness, and adapt to diverse work environments. The purpose of this study is to apply ROC and SMART methods in a Decision Support System (DSS) for the selection of the best waitress. Using the ROC, this study aimed to determine the relative weights of relevant criteria in waitress assessment, while SMART was used to provide a holistic approach in the evaluation of alternatives. The combination of these two methods is expected to provide a strong and measurable framework for selecting the best waitress, taking into account various aspects of qualifications and relevant preferences. The ranking results for the best waitress 1 with a final value of 0.8353 were obtained by Leni, for the best waitress 2 with a final value of 0.7163 obtained by Haris, and for the best waitress 3 with a final value of 0.6975 obtained by Riyadi.